Chondroblastoma with secondary aneurysmal bone cyst of the diaphyseal ulna: A rare case report - Gani Michel; Ahmad Fitrah; Atta Kuntara; M. Naseh Sajadi Budi Irawan (Radiology Case Reports)
Chondroblastomas are rare benign cartilaginous neoplasms that primarily affect young patients. Aneurysmal bone cysts (ABCs) are also rare, accounting for 1-2% of all bone tumors, and can arise either idiopathically or as secondary lesions associated with other tumors, such as giant cell tumors or chondroblastomas. Here, we present a rare case of a secondary aneurysmal bone cyst arising in conjunction with a chondroblastoma located in the left diaphysis of the ulna.